COVID-19 update: the first 6 months of the pandemic - Novelli, Giuseppe; Biancolella, Michela; Mehrian-Shai, Ruty; Erickson, Caroline; Godri Pollitt, Krystal J.; Vasiliou, Vasilis; Watt, Jessica; Reichardt, Juergen K. V. (Human genomics, 2020)
The COVID-19 pandemic is sweeping the world and will feature prominently in all our lives for months and most likely for years to come. We review here the current state 6 months into the declared pandemic. Specifically, we examine the role of the pathogen, the host and the environment along with the possible role of diabetes. We also firmly believe that the pandemic has shown an extraordinary light on national and international politicians whom we should hold to account as performance has been uneven. We also call explicitly on competent leadership of international organizations, specifically the WHO, UN and EU, informed by science. Finally, we also condense successful strategies for dealing with the current COVID-19 pandemic in democratic countries into a developing pandemic playbook and chart a way forward into the future. This is useful in the current COVID-19 pandemic and, we hope, in a very distant future again when another pandemic might arise.